«...BUT I DID NOT LIE...» To the 75th Anniversary of Olzhas O. Sulejmenov it is devoted - U M Bаkhtikireeva (RUDN Journal of Language Studies, Semiotics and Semantics, 2011)
The article is devoted to the 75th anniversary of Olzhas O. Sulejmenov. Opinions of the modern scientists on the scientific and creative activity of the researcher - philologist and the philosopher are presented.